Elbphilharmonie Visions : Concert with NDR Radiophilharmonie, Elbphilharmonie, Hamburg (DE) - Palmieri, Francesco ; 0009-0008-3147-2664 (Elbphilharmonie, 2025)
Performance featuring spherical amplification. Elbphilharmonie Visions Elbphilharmonie, Hamburg (DE) NDR Radiophilharmonie 14/02/2025 From the program: Iannotta, Clara (*1983, IT) – Moult (for orchestra) [2018-19]